Preparation method of green low-carbon composite cementitious material based on metallurgical solid waste
Patent Information
- Application Number
- CN202611327477.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-31
- Publication Date
- 2026-10-30
AI Technical Summary
[0006]本申请实施例提供一种基于冶金固废的绿色低碳复合胶凝材料制备方法,旨在克服现有技术中冶金固废利用率低、水泥熟料用量大、激发工艺复杂以及缺乏低碳性能等技术问题
[0017]本发明的有益效果是:通过将钢渣和高炉矿渣进行协同粉磨处理,实现了两种主要冶金固废的协同利用,显著提高了冶金固废的综合利用率至60%以上,有效解决了现有技术中钢渣利用率低的技术问题;通过采用硅酸钠、铝酸钠和氢氧化钙组成的复合固体激发剂,并采用低温烘干工艺简化了激发剂的制备过程,避免了现有技术中需要经过造粒、陈化、煅烧等多道复杂工序的问题;通过将复合固体激发剂的重量百分比控制在8%至15%,同时将脱硫石膏作为辅助组分引入体系,实现了冶金固废潜在活性的充分激发,显著提升了复合胶凝材料的胶凝性能;通过大幅降低水泥熟料的用量甚至不使用水泥熟料,有效降低了复合胶凝材料的碳排放,满足了绿色低碳的发展需求;通过各组分之间的协同作用,使得复合胶凝材料在28天抗压强度可达40MPa以上,具有良好的力学性能和耐久性能,为冶金固废的大规模资源化利用提供了一种切实可行的技术方案。
Smart Images

Figure CN123003169A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of building materials technology, and in particular to a method for preparing a green, low-carbon composite cementitious material based on metallurgical solid waste. Background Technology
[0002] With the acceleration of industrialization, the metallurgical industry generates a large amount of solid waste. The proper treatment and resource utilization of metallurgical solid wastes such as steel slag and blast furnace slag have become key issues restricting the green development of the steel industry. Composite cementitious materials, as an effective alternative to cement, have shown great potential in disposing of metallurgical solid waste and reducing carbon emissions. However, existing composite cementitious material preparation technologies still have many shortcomings in terms of metallurgical solid waste utilization efficiency, low-carbon performance, and cementing properties, requiring further improvement.
[0003] A search revealed a composite cementitious material and its preparation method, with publication number CN102633461B, published on October 9, 2013. This patent relates to a composite cementitious material, with the following weight ratio of raw materials: 28-55% blast furnace slag powder, 0-18% steel slag powder, 22-45% fly ash, 5-15% desulfurized gypsum, and 6-10% composite solid activator. While this technical solution utilizes metallurgical solid wastes such as blast furnace slag and steel slag, it has the following shortcomings: First, the utilization rate of steel slag is low, only 0-18%, failing to fully realize the potential for the large-scale disposal of metallurgical solid wastes; second, fly ash accounts for as much as 22-45% of the solution, indicating a high dependence on fly ash, which is not a metallurgical industry solid waste; third, the solution uses composite solid activators for activity activation, but does not specifically design activator formulations tailored to the characteristics of metallurgical solid wastes, making it difficult to fully activate the potential activity of metallurgical solid wastes; fourth, the patent does not explicitly propose low-carbon emission technologies, failing to meet the needs of green and low-carbon development.
[0004] A search revealed a patent with publication number CN116496011A, entitled "Activation Activator for Composite Cementitious Materials, Composite Cementitious Materials and Preparation Method thereof," published on July 28, 2023. This patent relates to an activation activator for composite cementitious materials, the preparation method of which includes mixing aluminum ash, phosphogypsum, regulating minerals, and water, granulating, and then aging and calcining to obtain the activation activator; the composite cementitious material comprises 20-30% activation activator, 60-70% cement clinker or steel slag, and 8-12% phosphogypsum. Although this technical solution involves the utilization of steel slag, it still has the following shortcomings: First, the solution uses cement clinker or steel slag, accounting for 60-70%, with cement clinker still as the main component. This fails to achieve a significant replacement of cement clinker, resulting in still high carbon emissions. Second, the solution uses an "or" expression, meaning it uses either cement clinker or steel slag, failing to achieve efficient synergistic utilization of cement clinker and metallurgical solid waste. Third, the preparation process of the active activator is relatively complex, requiring multiple steps such as granulation, aging, and calcination, increasing production costs and energy consumption. Fourth, although the solution utilizes solid wastes such as aluminum ash and phosphogypsum, the utilization methods for the most representative metallurgical solid wastes, such as steel slag and blast furnace slag, are relatively singular, failing to form a technical system for the synergistic utilization of diverse metallurgical solid wastes.
[0005] The aforementioned existing technical solutions indicate that current methods for preparing composite cementitious materials still have certain shortcomings in terms of metallurgical solid waste utilization rate, low-carbon performance, activation efficiency, and process simplification. Therefore, this invention provides a method for preparing green and low-carbon composite cementitious materials based on metallurgical solid waste, aiming to improve the comprehensive utilization rate of metallurgical solid waste, reduce cement clinker usage, simplify the activation process, and achieve truly green and low-carbon cementitious material preparation, thereby meeting the dual needs of resource utilization of metallurgical solid waste and low-carbon development of the cement industry. Summary of the Invention
[0006] This application provides a method for preparing green and low-carbon composite cementitious materials based on metallurgical solid waste, aiming to overcome the technical problems in the prior art, such as low utilization rate of metallurgical solid waste, large amount of cement clinker, complex activation process, and lack of low-carbon performance.
[0007] The first aspect of this application provides a method for preparing a green, low-carbon composite cementitious material based on metallurgical solid waste, comprising the following steps: Steel slag, blast furnace slag, fly ash, and desulfurized gypsum are used as raw material components. The steel slag and blast furnace slag are co-grinded to obtain a composite metallurgical solid waste powder. Sodium silicate, sodium aluminate, and calcium hydroxide are used as activator raw materials. The sodium silicate, sodium aluminate, and calcium hydroxide are mixed evenly and then dried at low temperature to obtain a composite solid activator. The composite metallurgical solid waste powder, the composite solid activator, and the remaining desulfurized gypsum are mixed evenly to obtain a composite cementitious material mixture. The composite cementitious material mixture is mixed with water and subjected to a hydration reaction to obtain a green low-carbon composite cementitious material.
[0008] Further, the co-grinding process specifically involves mixing the steel slag and the blast furnace slag in a weight ratio of 1:2 to 1:4, and then feeding them into a ball mill for grinding until the specific surface area is 400 to 600 m². 2 / kg, to obtain the composite metallurgical solid waste powder.
[0009] Further, the low-temperature drying process specifically involves: placing the mixed sodium silicate, sodium aluminate, and calcium hydroxide in an oven at a temperature of 80 to 120°C and drying them until the moisture content is less than 5%, then cooling them to room temperature and grinding them into powder to obtain the composite solid activator.
[0010] Furthermore, the weight percentage of each component in the composite solid activator is: sodium silicate 30% to 50%, sodium aluminate 20% to 40%, and calcium hydroxide 20% to 30%.
[0011] Furthermore, the weight percentage of the composite metallurgical solid waste powder is 60% to 80%; the weight percentage of the composite solid activator is 8% to 15%; and the weight percentage of the desulfurized gypsum is 10% to 20%.
[0012] In one optional embodiment, before taking steel slag, blast furnace slag, fly ash, and desulfurized gypsum as raw material components, the method further includes a pretreatment step for each raw material: the steel slag is subjected to magnetic separation to remove ferromagnetic substances, and then subjected to natural aging for 3 to 6 months; the blast furnace slag is dried until the moisture content is less than 2%; the fly ash is screened to remove coarse particles; and the desulfurized gypsum is crushed until the particle size is less than 5 mm.
[0013] In one optional embodiment, the hydration reaction specifically involves mixing the composite cementitious material mixture with water at a water-cement ratio of 0.25 to 0.40, and then curing it to a specified age at a temperature of 20 to 30°C and a relative humidity of not less than 90%.
[0014] In one optional embodiment, the chemical composition of the steel slag by weight percentage is: CaO 40% to 50%, SiO2 15% to 25%, Al2O3 2% to 8%, Fe2O3 5% to 15%, MgO 3% to 10%; and the chemical composition of the blast furnace slag by weight percentage is: CaO 30% to 42%, SiO2 25% to 35%, Al2O3 10% to 18%, MgO 5% to 12%.
[0015] In one alternative embodiment, the sodium silicate has a modulus of 2.8 to 3.2; and the sodium aluminate has an Al2O3 content of 40% to 50%.
[0016] In an optional embodiment, the step of adding a water-reducing agent during the hydration reaction is further included, wherein the weight of the water-reducing agent is 0.5% to 1.5% of the weight of the composite cementitious material mixture.
[0017] The beneficial effects of this invention are as follows: By co-grinding steel slag and blast furnace slag, the co-utilization of two major metallurgical solid wastes is achieved, significantly improving the comprehensive utilization rate of metallurgical solid waste to over 60%, effectively solving the technical problem of low steel slag utilization in existing technologies; by using a composite solid activator composed of sodium silicate, sodium aluminate, and calcium hydroxide, and employing a low-temperature drying process, the preparation process of the activator is simplified, avoiding the problems of multiple complex processes such as granulation, aging, and calcination required in existing technologies; by controlling the weight percentage of the composite solid activator to 8% or higher... The composite cementitious material contains 15% desulfurized gypsum as an auxiliary component, which fully activates the potential activity of metallurgical solid waste and significantly improves its cementitious performance. By significantly reducing the amount of cement clinker or even eliminating it altogether, the carbon emissions of the composite cementitious material are effectively reduced, meeting the needs of green and low-carbon development. Through the synergistic effect between the components, the composite cementitious material achieves a compressive strength of over 40 MPa after 28 days, exhibiting excellent mechanical and durability properties, providing a practical technical solution for the large-scale resource utilization of metallurgical solid waste. Attached Figure Description
[0018] Figure 1 This is a schematic diagram of the overall technical solution architecture of the method for preparing green and low-carbon composite cementitious materials based on metallurgical solid waste proposed in this invention. Figure 2 This is a schematic diagram illustrating the core principle framework of the synergistic effect between the composite solid activator and metallurgical solid waste powder in this invention. Detailed Implementation
[0019] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0020] Specific implementation examples are given below.
[0021] Reference Figure 1 , Figure 1 This is a schematic diagram of the overall technical solution architecture of a method for preparing green and low-carbon composite cementitious materials based on metallurgical solid waste, as proposed in an embodiment of this application. As shown in the figure, the method includes the following four core steps: preparation of composite metallurgical solid waste powder, preparation of composite solid activator, preparation of composite cementitious material mixture, and hydration reaction.
[0022] In this embodiment, the preparation of green and low-carbon composite cementitious material based on metallurgical solid waste begins with raw material pretreatment. Steel slag, blast furnace slag, fly ash, and desulfurized gypsum are used as raw material components. The steel slag and blast furnace slag are co-milled according to a set weight ratio to obtain composite metallurgical solid waste powder. Simultaneously, sodium silicate, sodium aluminate, and calcium hydroxide are used as activator raw materials. After uniform mixing, the three are subjected to low-temperature drying to obtain a composite solid activator. Subsequently, the composite metallurgical solid waste powder, the composite solid activator, and the remaining desulfurized gypsum are mixed uniformly according to a set weight percentage to obtain a composite cementitious material mixture. Finally, the composite cementitious material mixture is mixed with water according to a set water-cement ratio and subjected to a hydration reaction. It is then cured to a specified age under set temperature and humidity conditions to obtain the green and low-carbon composite cementitious material.
[0023] This application achieves the synergistic utilization of two major metallurgical solid wastes through the co-grinding treatment of steel slag and blast furnace slag, significantly improving the comprehensive utilization rate of metallurgical solid waste to over 60%, and effectively solving the technical problem of low steel slag utilization in the prior art. By using a composite solid activator composed of sodium silicate, sodium aluminate and calcium hydroxide, and adopting a low-temperature drying process, the preparation process of the activator is simplified, avoiding the problems of multiple complex processes such as granulation, aging and calcination required in the prior art.
[0024] One embodiment: A method for preparing composite metallurgical solid waste powder In this method, the co-grinding process specifically involves mixing steel slag and blast furnace slag at a weight ratio of 1:2 to 1:4, and then feeding the mixture into a ball mill for grinding until the specific surface area reaches 400 to 600 m². 2 / kg, to obtain composite metallurgical solid waste powder.
[0025] In this embodiment, co-grinding is a key step in achieving efficient utilization of metallurgical solid waste. First, steel slag and blast furnace slag are mixed in a weight ratio of 1:2 to 1:4. This weight ratio range is determined based on the following technical considerations: When the weight ratio of steel slag to blast furnace slag is 1:2, the composite powder has a higher proportion of steel slag, which is beneficial for leveraging the cementitious activity of dicalcium silicate (C2S) and tricalcium silicate (C3S) in the steel slag. Simultaneously, the glassy structure of the blast furnace slag can effectively fill the pores between steel slag particles. When the weight ratio reaches 1:4, the proportion of blast furnace slag increases, and its rich Al2O3 content can form more hydration products such as calcium aluminum feldspar (C2AS) with CaO in the steel slag, enhancing the mechanical strength of the system. An intermediate ratio, such as 1:3, balances the early strength contribution of steel slag and the long-term strength contribution of blast furnace slag.
[0026] In this embodiment, the mixed steel slag and blast furnace slag are fed into a ball mill for grinding. The grinding media in the ball mill are alumina grinding balls with a diameter of 20 mm to 40 mm, the ball-to-material ratio is 5:1 to 8:1, and the grinding time is 60 to 120 minutes. During the grinding process, the impact and shearing action of the grinding balls gradually refines the steel slag and blast furnace slag particles, causing lattice distortion on the particle surface and deagglomeration of the glassy structure, exposing more active silicon and aluminum sites. The grinding process is repeated until the specific surface area is 400 to 600 m². 2 At a density of 10 μm / kg, the average particle size (D50) is approximately 10 μm to 25 μm. The increase in specific surface area significantly increases the reaction interface between the particles and the activator.
[0027] In this embodiment, the lower limit of specific surface area is set to 400 m². 2 / kg, ensuring the particles are fine enough to fully activate their potential activity; the upper limit is set at 600 m 2 / kg, to avoid over-grinding that leads to particle agglomeration and excessive energy consumption. When the specific surface area is 400 m² 2 At / kg, the particle surface energy is approximately 50 mJ / m 2 When the specific surface area increases to 600 m² 2 At / kg, the particle surface energy can reach 75 mJ / m 2 The increase in surface energy significantly promotes the subsequent hydration reaction.
[0028] One embodiment: A method for preparing a composite solid activator In this method, the low-temperature drying process specifically involves placing the mixed sodium silicate, sodium aluminate, and calcium hydroxide in an oven at a temperature of 80°C to 120°C and drying them until the moisture content is less than 5%. Then, the mixture is cooled to room temperature and ground into powder to obtain a composite solid activator.
[0029] In this embodiment, the composite solid activator is prepared using a low-temperature drying process. Compared with the multiple steps of granulation, aging, and calcination in the prior art, this process significantly simplifies the production process and reduces energy consumption. First, sodium silicate, sodium aluminate, and calcium hydroxide are mixed according to a set weight percentage, wherein sodium silicate accounts for 30% to 50%, sodium aluminate accounts for 20% to 40%, and calcium hydroxide accounts for 20% to 30%.
[0030] Sodium silicate provides SiO4 in the system 4- The tetrahedral structural unit has a modulus (molar ratio of SiO2 to Na2O) controlled between 2.8 and 3.2. Too low a modulus leads to excessive alkalinity, inhibiting the hydration reaction; too high a modulus leads to excessive alkalinity in SiO4. 4- Tetrahedral polymerization is too high, making it difficult to dissolve and participate in the reaction. Sodium aluminate provides AlO4 in the system. 5- The tetrahedral structural unit has an Al₂O₃ content controlled between 40% and 50%. Too low an Al₂O₃ content will lead to insufficient AlO₄ content in the system. 5- Insufficient tetrahedral concentration makes it difficult to form enough hydrated aluminate products; excessive Al₂O₃ content leads to overly vigorous reaction, producing too much hydrated calcium aluminate crystals and affecting the stability of the system. Calcium hydroxide provides OH⁻ in the system. - and Ca 2+ The solubility of ions directly affects the alkalinity level of the system. The addition of calcium hydroxide can maintain the pH value of the system in the range of 12.5 to 13.5. This alkaline environment is sufficient to cause the glass structure in the metallurgical solid waste powder to depolymerize.
[0031] In this embodiment, the mixed activator raw materials are placed in an oven at a temperature of 80°C to 120°C for low-temperature drying, with the drying time controlled between 2 and 4 hours, until the moisture content of the activator mixture is less than 5%. When the moisture content is higher than 5%, the powder is prone to clumping, affecting subsequent uniform mixing; when the moisture content is lower than 5%, the powder remains loose, facilitating uniform mixing with metallurgical solid waste powder.
[0032] The drying temperature is set at 80℃ to 120℃ because this temperature range is sufficient to remove free water and water of crystallization from the raw materials, while avoiding decomposition or crystal transformation of sodium silicate and sodium aluminate due to high temperatures. At 80℃, sodium silicate remains amorphous and exhibits the highest reactivity. When the drying temperature rises to 120℃, calcium hydroxide partially decomposes to form calcium oxide (CaO). Calcium oxide then rehydrates to form calcium hydroxide during subsequent hydration, releasing a large amount of heat and promoting early strength development of the system. After drying, the activator mixture is cooled to room temperature (20℃ ± 5℃) and then ground in a ball mill until the particle size is less than 100 μm, obtaining a composite solid activator. The grinding process breaks up particle agglomerates, ensuring thorough and uniform mixing of the components, improving the dispersibility and reaction efficiency of the activator.
[0033] One embodiment: A method for preparing a composite cementitious material mixture In this method, the weight percentages of each component are: 60% to 80% composite metallurgical solid waste powder, 8% to 15% composite solid activator, and 10% to 20% desulfurized gypsum.
[0034] In this embodiment, the proportioning design of the composite cementitious material mixture is the core to achieving optimal cementitious performance. The composite metallurgical solid waste powder serves as the main cementitious component, with its weight percentage set at 60% to 80%. This range ensures sufficient sources of active SiO2 and Al2O3 in the system. When the weight percentage of the composite metallurgical solid waste powder is below 60%, the amount of cementitious phase generated in the system is insufficient, making it difficult to form a dense hydration product structure. When the weight percentage is above 80%, the amount of activator is relatively insufficient, failing to fully activate the potential activity of the metallurgical solid waste.
[0035] The weight percentage of the composite solid activator is set at 8% to 15%, a range that ensures a sufficient supply of alkali metal ions (Na+). + ) and hydroxide ions (OH) - This process disrupts the vitreous structure of metallurgical solid waste while providing soluble silica and aluminate ions to participate in the hydration reaction. When the weight percentage of the activator is less than 8%, the alkalinity of the system is insufficient, resulting in a low degree of activation of the metallurgical solid waste. When the weight percentage is greater than 15%, there is too much unreacted activator residue in the system, which not only wastes resources but may also lead to efflorescence in the later stages.
[0036] Desulfurized gypsum is used as an auxiliary component, with a weight percentage set at 10% to 20%. The main component of desulfurized gypsum is CaSO4·2H2O, which provides SO42-. 2-Ions can react with aluminates in the system to form ettringite (AFt) phase. The formation of the AFt phase can fill pores, improve strength, and inhibit alkali-aggregate reaction. When the weight percentage of desulfurized gypsum is less than 10%, the amount of AFt phase formed is insufficient to effectively fill pores; when the weight percentage is greater than 20%, excessive SO4... 2- This can lead to excessive growth of the AFt phase, generating expansion stress and affecting the stability of the system.
[0037] In this embodiment, the composite metallurgical solid waste powder, composite solid activator, and desulfurization gypsum are weighed according to the above-mentioned weight percentages and then added to a concrete mixer for dry mixing. The mixing time is 5 to 10 minutes to ensure uniform distribution of each component. After dry mixing is completed, the mixture is transferred to a storage tank for later use.
[0038] In one optional embodiment, a water-reducing agent may be added during the mixing process, the water-reducing agent being 0.5% to 1.5% of the weight of the composite cementitious material mixture. The addition of the water-reducing agent can reduce the water-cement ratio and improve the fluidity and density of the cementitious material. The water-reducing agent can be a polycarboxylate-based high-performance water-reducing agent, whose molecular structure contains carboxylic acid groups (COO). - It can be adsorbed on the surface of cement particles, generating electrostatic repulsion and steric hindrance effect, so that the particles are evenly dispersed.
[0039] One implementation method: Raw material pretreatment method In this method, before using steel slag, blast furnace slag, fly ash, and desulfurized gypsum as raw material components, a pretreatment step is also included for each raw material: the steel slag is subjected to magnetic separation to remove ferromagnetic substances, and then subjected to natural aging for 3 to 6 months; the blast furnace slag is dried until the moisture content is less than 2%; the fly ash is screened to remove coarse particles; and the desulfurized gypsum is crushed until the particle size is less than 5 mm.
[0040] In this embodiment, raw material pretreatment is a crucial step in ensuring the stability of the final cementitious material's performance. The steel slag pretreatment includes two steps: First, magnetic separation, which removes ferromagnetic substances (such as iron blocks and filings) from the steel slag using a magnetic separator. The magnetic field strength is set to 1000 Gauss to 1500 Gauss, and the magnetic separation speed is set to 30 r / min to 50 r / min. After magnetic separation, the ferromagnetic substance content in the steel slag can be reduced to below 0.5%. Second, natural aging, where the magnetically separated steel slag is piled up in a natural environment for 3 to 6 months. During natural aging, the free calcium oxide (f-CaO) and free magnesium oxide (f-MgO) in the steel slag gradually absorb moisture from the air and undergo a digestion reaction, generating calcium hydroxide and magnesium hydroxide, with volume expansion rates of 107.9% and 148%, respectively. Natural aging effectively avoids volume stability problems caused by the hydration expansion of f-CaO and f-MgO during subsequent hydration processes. After natural aging for 3 months, the f-CaO content in steel slag can be reduced to below 3%; after aging for 6 months, the f-CaO content can be reduced to below 1%.
[0041] In this embodiment, the pretreatment of blast furnace slag involves drying. The blast furnace slag is placed in a drying oven and heated to 100°C to 105°C until the moisture content is below 2%. Excessive moisture content in blast furnace slag can cause it to easily clump during storage and grinding, and also affect the uniformity of subsequent mixing with the activator. When the moisture content of the blast furnace slag exceeds 2%, a water film forms on the particle surface, hindering direct contact between the activator and the particle surface, thus reducing the activation effect.
[0042] The pretreatment of fly ash involves sieving, using a standard sieve (45 μm aperture) to remove coarse particles larger than 45 μm. The coarse particles in fly ash are mostly unburned carbon particles and porous glass, which have low activity. Sieving removes these inert components and improves the overall activity of the cementitious material.
[0043] The pretreatment of desulfurized gypsum involves crushing it to a particle size of less than 5 mm using a jaw crusher. Crushing increases the specific surface area of the desulfurized gypsum, promoting its dissolution and participation in the hydration reaction.
[0044] One implementation method: hydration reaction method In this method, the hydration reaction specifically involves mixing the composite cementitious material mixture with water at a water-cement ratio of 0.25 to 0.40, and then curing it at a temperature of 20°C to 30°C and a relative humidity of not less than 90% until the specified age.
[0045] In this embodiment, the hydration reaction is the key step in achieving strength in the composite cementitious material. First, the composite cementitious material mixture is mixed with water at a water-cement ratio of 0.25 to 0.40. Setting the water-cement ratio requires balancing two conflicting indicators: fluidity and strength. When the water-cement ratio is below 0.25, the slurry is too viscous and difficult to cast densely; when the water-cement ratio is above 0.40, excessive free water will evaporate during hydration, leaving capillary pores and reducing the material's density and strength. In this embodiment, a water-cement ratio of 0.30 to 0.35 is preferred. Within this range, the slurry has suitable fluidity while forming a dense hydration product structure.
[0046] In this embodiment, a cement mortar mixer is used for the mixing process. First, the composite cementitious material mixture is added to the mixing pot and dry-mixed for 2 to 3 minutes to ensure uniform mixing. Then, a set amount of water is added and wet-mixed for 3 to 5 minutes to form a uniform slurry. During the mixing process, it is important to add enough water at once to avoid uneven water-cement ratios caused by adding water in stages. After mixing, the slurry is poured into a standard 70.7 mm × 70.7 mm × 70.7 mm cube mold and vibrated to remove air bubbles. After molding, the specimens are allowed to stand at room temperature for 24 to 48 hours before demolding. The demolded specimens are immediately placed in a standard curing chamber for curing.
[0047] In this embodiment, the curing conditions are set at a temperature of 20°C to 30°C and a relative humidity of not less than 90%. Temperature is a key factor affecting the hydration reaction rate: when the curing temperature is below 20°C, the hydration reaction rate decreases significantly, and strength development is slow; when the curing temperature is above 30°C, the hydration reaction rate is too fast, and the early hydration products are unevenly distributed, which may lead to a decline in strength later. A relative humidity of not less than 90% is to prevent surface moisture evaporation and ensure the hydration reaction continues. When the relative humidity is below 90%, the rate of surface moisture evaporation is greater than the rate of internal moisture migration to the surface, which leads to increased capillary negative pressure, resulting in self-drying shrinkage, and in severe cases, cracking.
[0048] After curing to the specified age (e.g., 3 days, 7 days, 28 days), compressive strength tests are conducted. The green low-carbon composite cementitious material prepared in this application can achieve a compressive strength of over 40 MPa after 28 days, meeting the strength requirements of ordinary Portland cement.
[0049] One implementation method: The mechanism of synergistic effect between activator and metallurgical solid waste powder Reference Figure 2 , Figure 2 This is a schematic diagram illustrating the core principle framework of the synergistic effect between the composite solid activator and metallurgical solid waste powder in this invention.
[0050] In this embodiment, the synergistic mechanism between the composite solid activator and the metallurgical solid waste powder can be explained in detail at the microscopic level. The synergistic process consists of three stages: the first stage is the alkaline activation stage, the second stage is the ion exchange and adsorption stage, and the third stage is the hydration product generation and structural compaction stage.
[0051] In the first alkaline activation stage, after the composite solid activator dissolves in water, sodium silicate (Na2O·nSiO2) hydrolyzes to generate Na + OH - and soluble silicate ions (SiO4) 4- Sodium aluminate (NaAlO2) hydrolyzes to produce Na + OH - and soluble aluminate ions (AlO2) - ), calcium hydroxide (Ca(OH)2) dissolves to form Ca 2+ and OH - The pH of the system rapidly increased to 12.5 to 13.5, and the OH- - Ions attack the glassy structure on the surface of metallurgical solid waste powders (mainly steel slag and blast furnace slag), causing the Si-O-Si and Al-O-Al bonds to break and generating a large number of active silicon-oxygen tetrahedra ([SiO4)). 4- ) and aluminum-oxygen tetrahedron ([AlO4]) 5- The reaction at this stage can be represented by the following chemical equation: Na₂O·nSiO₂ + H₂O → 2Na + + 2OH - + nSiO4 4- NaAlO2 + H2O → Na + + OH - + AlO2 - Ca(OH)2→ Ca 2+ + 2OH - Si-O-Si + OH - → Si-O - + HO-Si Al-O-Al + OH - → Al-O - + HO-Al In the second stage of ion exchange and adsorption, the activator provides Na + and Ca 2+Ions exchange with cations on the surface of metallurgical solid waste powder particles, altering the double-layer structure of the particle surface, lowering the zeta potential, weakening the electrostatic repulsion between particles, and causing particle aggregation. Simultaneously, active silicon-oxygen tetrahedra and aluminum-oxygen tetrahedra in the activator adsorb onto the surface of the metallurgical solid waste powder particles, forming a gel-like transition zone. This transition zone serves as a nucleation site for the subsequent growth of hydration products and can significantly promote their formation.
[0052] In the third stage of hydration product formation and structural compaction, active silicon-oxygen tetrahedra and aluminum-oxygen tetrahedra react with Ca... 2+ OH - Ions undergo hydration reactions to generate a series of hydrated calcium silicate (CSH) gels and hydrated calcium aluminate (CAH) gels. The chemical formula of CSH gel can be represented as (CaO)1.7SiO2(H2O)1.8, and it exhibits a fibrous or network structure, effectively filling the pores between particles. The chemical formula of CAH gel can be represented as C3AH6 or C4AH. 13 It has a plate-like or columnar structure, which can interweave and overlap with CSH gel to form a dense three-dimensional spatial network structure.
[0053] Meanwhile, the SO4 provided by desulfurization gypsum 2- The ions react with aluminates to form ettringite (AFt) phase, with the chemical formula C6AȘ3H. 32 The AFt phase exists as needle-like crystals, which can cross-laminate to further compact the structure. The reaction equation is as follows: Ca 2+ + [SiO4] 4- + H2O → CSH Ca 2+ + [AlO4] 5- + H2O → CAH C3A + 3Ș + 26H → C6AȘ3H 32 In this embodiment, through the synergistic effect of the above three stages, the composite cementitious material system forms a dense hydration product structure, and the compressive strength after 28 days can reach more than 40 MPa. Compared with the prior art, this application achieves full activation of the potential activity of metallurgical solid waste through the synergistic effect of sodium silicate, sodium aluminate and calcium hydroxide in the composite solid activator, avoiding the problems of low activation efficiency and subsequent strength reduction that exist with single activators.
[0054] One implementation method: Chemical composition of steel slag and blast furnace slag In this embodiment, the chemical composition of the steel slag by weight percentage is: CaO 40% to 50%, SiO2 15% to 25%, Al2O3 2% to 8%, Fe2O3 5% to 15%, MgO 3% to 10%; the chemical composition of the blast furnace slag by weight percentage is: CaO 30% to 42%, SiO2 25% to 35%, Al2O3 10% to 18%, MgO 5% to 12%.
[0055] In this embodiment, the chemical composition of steel slag and blast furnace slag determines their potential cementitious activity. The steel slag contains 40% to 50% CaO, mainly derived from the decomposition products of limestone (CaCO3). CaO is the main component in the formation of C3S and C2S, and under alkaline activation, it can hydrate to form CSH gel, providing cementitious strength. The SiO2 content is 15% to 25%, mainly existing in the form of C2S and C3S, and is the main source of cementitious activity. The Al2O3 content is 2% to 8%, which can participate in the formation of CAH gel and ettringite. The Fe2O3 content is 5% to 15%, mainly forming aluminoferrite phases such as C2F and C4AF, which also have certain hydration activity under alkaline conditions. The MgO content is 3% to 10%, mainly existing in the form of RO phase (MgO-FeO solid solution) or free MgO. Appropriate amounts of MgO can improve the sulfate resistance of the material, but excessive MgO can lead to volume stability problems, thus requiring natural aging treatment to eliminate these issues.
[0056] In this embodiment, the CaO content in the blast furnace slag is 30% to 42%, mainly existing in a glassy form, which can hydrate to form CSH gel under alkaline activation; the SiO2 content is 25% to 35%, also existing in a glassy form, and is the main source of cementitious activity; the Al2O3 content is 10% to 18%, a relatively high content, which can generate a large amount of CAH gel and ettringite under alkaline activation, improving early strength; the MgO content is 5% to 12%, mainly existing in a glassy form, and an appropriate amount of MgO can improve the heat resistance and later strength of the material. The glassy content of blast furnace slag is usually above 80%, and the glassy structure consists of [SiO4]. 4- and [AlO4] 5- Tetrahedrons form a network, and the network-forming agent (Ca) 2+ Mg 2+ (etc.) fill the gaps in the network, and the OH in the alkaline activator - It can disrupt the network structure, causing the vitreous body to depolymerize and release active silicon and aluminum ions, which then participate in the hydration reaction.
[0057] The method for preparing green and low-carbon composite cementitious materials based on metallurgical solid waste proposed in this application has the following significant advantages: The comprehensive utilization rate of metallurgical solid waste has been significantly improved: by co-grinding steel slag and blast furnace slag, the co-utilization of the two main metallurgical solid wastes has been achieved, and the comprehensive utilization rate of metallurgical solid waste can reach more than 60%, which effectively solves the technical problem of low utilization rate of steel slag (usually less than 20%) in the existing technology.
[0058] Simplified activation process: The composite solid activator composed of sodium silicate, sodium aluminate and calcium hydroxide is used, and the low temperature drying process (80℃ to 120℃) simplifies the preparation process of the activator, avoiding the problems of multiple complex processes such as granulation, aging and calcination required in the existing technology, and reducing energy consumption and production costs.
[0059] Excellent gelling performance: By controlling the weight percentage of the composite solid activator to 8% to 15% and introducing desulfurized gypsum as an auxiliary component into the system, the potential activity of metallurgical solid waste is fully activated, and the compressive strength after 28 days can reach more than 40MPa, exhibiting good mechanical properties and durability.
[0060] Low-carbon and environmentally friendly: By significantly reducing the amount of cement clinker used or even eliminating it altogether, the carbon emissions of composite cementitious materials are effectively reduced. Each ton of cementitious material can reduce CO2 emissions by approximately 0.5 to 0.8 tons, meeting the needs of green and low-carbon development.
[0061] The various embodiments in this specification are described in a progressive manner, with each embodiment focusing on the differences from other embodiments. The same or similar parts between the various embodiments can be referred to each other.
[0062] Those skilled in the art will understand that embodiments of this application can be provided as methods, apparatus, or computer program products. Therefore, embodiments of this application can take the form of entirely hardware embodiments, entirely software embodiments, or embodiments combining software and hardware aspects. Furthermore, embodiments of this application can take the form of computer program products implemented on one or more computer-usable storage media (including but not limited to disk storage, CD-ROM, optical storage, etc.) containing computer-usable program code.
[0063] This application describes embodiments with reference to flowchart illustrations and / or block diagrams of methods, terminal devices (systems), and computer program products according to embodiments of this application. It should be understood that each block of the flowchart illustrations and / or block diagrams, and combinations of blocks in the flowchart illustrations and / or block diagrams, can be implemented by computer program instructions. These computer program instructions can be provided to a processor of a general-purpose computer, special-purpose computer, embedded processor, or other programmable data processing terminal device to produce a machine, such that the instructions, which execute via the processor of the computer or other programmable data processing terminal device, generate instructions for implementing the flowchart illustrations. Figure 1One or more processes and / or boxes Figure 1 A device that provides the functions specified in one or more boxes.
[0064] These computer program instructions may also be stored in a computer-readable storage medium that can direct a computer or other programmable data processing terminal device to operate in a particular manner, such that the instructions stored in the computer-readable storage medium produce an article of manufacture including instruction means, which are implemented in a process Figure 1 One or more processes and / or boxes Figure 1 The function specified in one or more boxes.
[0065] These computer program instructions can also be loaded onto a computer or other programmable data processing terminal equipment, causing a series of operational steps to be performed on the computer or other programmable terminal equipment to produce a computer-implemented process, thereby providing instructions that execute on the computer or other programmable terminal equipment for implementing the process. Figure 1 One or more processes and / or boxes Figure 1 The steps of the function specified in one or more boxes.
[0066] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A method for preparing a green, low-carbon composite cementitious material based on metallurgical solid waste, characterized in that, Includes the following steps: Steel slag, blast furnace slag, fly ash, and desulfurized gypsum are used as raw material components. The steel slag and blast furnace slag are co-grinded to obtain a composite metallurgical solid waste powder. Sodium silicate, sodium aluminate, and calcium hydroxide are used as activator raw materials. The sodium silicate, sodium aluminate, and calcium hydroxide are mixed evenly and then dried at low temperature to obtain a composite solid activator. The composite metallurgical solid waste powder, the composite solid activator, and the remaining desulfurized gypsum are mixed evenly to obtain a composite cementitious material mixture. The composite cementitious material mixture is mixed with water and subjected to a hydration reaction to obtain a green low-carbon composite cementitious material.
2. The preparation method according to claim 1, characterized in that, The co-grinding process specifically involves mixing the steel slag and the blast furnace slag in a weight ratio of 1:2 to 1:4, and then grinding them in a ball mill until the specific surface area is 400 to 600 m². 2 / kg, to obtain the composite metallurgical solid waste powder.
3. The preparation method according to claim 1, characterized in that, The low-temperature drying process specifically involves placing the mixed sodium silicate, sodium aluminate, and calcium hydroxide in an oven at a temperature of 80 to 120°C and drying them until the moisture content is less than 5%. Then, the mixture is cooled to room temperature and ground into powder to obtain the composite solid activator.
4. The preparation method according to claim 1, characterized in that, The weight percentages of each component in the composite solid activator are as follows: sodium silicate 30% to 50%, sodium aluminate 20% to 40%, and calcium hydroxide 20% to 30%.
5. The preparation method according to claim 1, characterized in that, The composite metallurgical solid waste powder has a weight percentage of 60% to 80%; the composite solid activator has a weight percentage of 8% to 15%; and the desulfurized gypsum has a weight percentage of 10% to 20%.
6. The preparation method according to claim 1, characterized in that, Before using steel slag, blast furnace slag, fly ash, and desulfurized gypsum as raw material components, the process includes a pretreatment step for each raw material: the steel slag is subjected to magnetic separation to remove ferromagnetic substances, followed by natural aging for 3 to 6 months; the blast furnace slag is dried until its moisture content is below 2%. The fly ash is screened to remove coarse particles; the desulfurized gypsum is crushed to a particle size of less than 5 mm.
7. The preparation method according to claim 1, characterized in that, The hydration reaction specifically involves mixing the composite cementitious material mixture with water at a water-cement ratio of 0.25 to 0.40, and then curing it to the specified age at a temperature of 20 to 30°C and a relative humidity of not less than 90%.
8. The preparation method according to claim 1, characterized in that, The chemical composition of the steel slag by weight percentage is: CaO 40% to 50%, SiO2 15% to 25%, Al2O3 2% to 8%, Fe2O3 5% to 15%, MgO 3% to 10%; the chemical composition of the blast furnace slag by weight percentage is: CaO 30% to 42%, SiO2 25% to 35%, Al2O3 10% to 18%, MgO 5% to 12%.
9. The preparation method according to claim 1, characterized in that, The sodium silicate has a modulus of 2.8 to 3.2; the sodium aluminate has an Al2O3 content of 40% to 50%.
10. The preparation method according to claim 1, characterized in that, The hydration reaction process also includes the step of adding a water-reducing agent, wherein the weight of the water-reducing agent is 0.5% to 1.5% of the weight of the composite cementitious material mixture.
Citation Information
Patent Citations
Composite gel material and preparation method thereof
CN102633461B
Active exciting agent for composite cementing material, composite cementing material and preparation method of composite cementing material
CN116496011A